Assessment of Quality of Life for Patients with Diabetes Mellitus (type II) (Journal of the College of Basic Education, 2023)
Objectives: The purpose of the study was to investigate the quality of life for patients with diabetes mellitus (type II) in Baghdad city.Methodology: A purposive (non-probability) sampling of 100 patient with diabetes mellitus who attending to the medical public clinics in Baghdadcity. Data was obtained through the interview for patients.A questionnaire was adopted from the medical outcomes study short form36(MOS- SF36). The questionnaire was to Arabic language and then exposed to a panel of experts-. Data were analyzed through the application of descriptive the inferential data analysis approach.